2020
DOI: 10.1097/mpg.0000000000002873
|View full text |Cite
|
Sign up to set email alerts
|

Nephrocalcinosis and Renal Dysfunction in Pediatric Intestinal Failure

Abstract: Background: Outcomes of pediatric intestinal failure (PIF) have improved recently, with other comorbidities, such as increased echogenicity/nephrocalcinosis on ultrasound (US) in long-term survivors now evident. We evaluated the significance of nephrocalcinosis over time in PIF and its impact on renal function. Methods: Retrospective analysis on a cohort of PIF patients was performed. Presence of nephrocalcinosis and/or increased renal echogenicity (ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…As evidence of this, despite the high frequency of calciuria and hypocitraturia, nephrocalcinosis or renal stones were infrequent in our cohort. The rates of hypercalciuria, hypocitraturia and hyperoxaluria in our study were all slightly above the rates described recently in the pediatric cohort published by Roberts et al [11], in which the patients were younger and with a lesser duration of chronic PN treatment. The latter study, however, reported a higher incidence of nephrocalcinosis than described in our study.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…As evidence of this, despite the high frequency of calciuria and hypocitraturia, nephrocalcinosis or renal stones were infrequent in our cohort. The rates of hypercalciuria, hypocitraturia and hyperoxaluria in our study were all slightly above the rates described recently in the pediatric cohort published by Roberts et al [11], in which the patients were younger and with a lesser duration of chronic PN treatment. The latter study, however, reported a higher incidence of nephrocalcinosis than described in our study.…”
Section: Discussionsupporting
confidence: 75%
“…The median (IQR) daily volume of the PN bags was 1200 (950-1550) mL. All patients used a cycling PN schedule at night, with a median (IQR) infusion duration of 11(10)(11)(12) h. All consumed oral or enteral nutrition during daytime as tolerated. PN provided median (IQR) energy per body weight of 50 (40.2-59.5) kcal/kg/day.…”
mentioning
confidence: 99%
“…Once a condition with a high mortality, pediatric intestinal failure is now considered a complex but survivable disorder 3 . The introduction of multidisciplinary teams and novel therapies has resulted in improved outcomes, 4 but children with intestinal failure remain at risk for multiple comorbidities and significant complications 5–10 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 With improved survival, additional complications have emerged. [3][4][5][6] Recent data indicate that the body composition of children with IF is abnormal with a relatively high fat mass (FM) and low fat-free mass (FFM) when compared with healthy children. [7][8][9][10][11] Most concerning is that abnormal body composition is present in both normal and abnormally growing children with IF based on weight-for-age (WFA) and height-for-age (HFA) z scores.…”
Section: Introductionmentioning
confidence: 99%